Numerical Simulation of Flow and Heat Transfer Characteristics of CuO-Water Nanofluids in a Flat Tube - She, Luchao; Fan, Guangming (Frontiers in Energy Research, 2018)
In this paper, water and CuO-water nanofluids are selected as working fluids. The characteristics of fluid flow and heat transfer in a heat transfer tube are analyzed by means of numerical simulation. The effect of nanofluid concentration on the flow and heat transfer characteristics of the flat tube under the condition with a Reynolds number of 6000~10000 is analyzed and compared with that of the circular tube. The results show that the addition of nanoparticles in the nanofluid has little effect on the velocity and temperature distribution in the flow channel. With the increase of nanofluid concentration, the heat transfer coefficient and flow resistance of the fluid increased. And the comprehensive evaluation factor was 2.51~3.29, which had the effect of enhancing heat exchange. There is a similar trend in the same concentration with different Reynolds numbers. Compared with the circular tube, the nanofluid has a better ability to enhance heat transfer when it flows in the flat tube. Under conditions with the same fluid concentration, the effect of the application of the nanofluids on the flat tube is better.